Nomenclatural correction in Cryptanthus Otto & A. Dietrich. (Bromeliaceae - Bromelioideae) - Alves,Marccus (2015)
Abstract Nomenclatural correction in Cryptanthus Otto & A. Dietrich. (Bromeliaceae - Bromelioideae). A nomenclatural correction of the author name of Cryptanthus zonatus, an endemic species of Northeastern Brazil, is provided. A new synonym of this species is also proposed.